The pitch code in music as compared with the natural language code - RAKOWSKI, Andrzej (Archives of Acoustics, 1988)
Comparisons are drawn between the formal features of language and music. Basic phonological universals of language and music are compared. Attention is drawn to specific properties of sound material and the general features of human perception mechanisms in the process of aural communication. The general common rules are described governing the organisation of communication codes in language and music.